Analysis of Fecal Lactobacillus Community Structure in Patients with Early Rheumatoid Arthritis - Liu, Xiaofei; Zou, Qinghua; Zeng, Benhua; Fang, Yongfei; Wei, Hong (Current microbiology, 2013)
The objective of this study was to analyze human fecal Lactobacillus community and its relationship with rheumatoid arthritis. Samples taken from rheumatoid arthritis (RA) patients and healthy individuals were analyzed by quantitative real-time PCR. Bacterial DNA was extracted from feces, and amplicons of the Lactobacillus-specific regions of 16S rRNA were analyzed by denaturing gradient gel electrophoresis. The richness, Shannon-Wiener index, and evenness of gut microbiota of both groups were analyzed to compare fecal Lactobacillus community structures. Results of this study demonstrated that fecal microbiota of RA patients contained significantly more Lactobacillus (10.62 ± 1.72 copies/g) than the control group (8.93 ± 1.60 copies/g). Significant increases were observed in RA patients in terms of the richness, Shannon-Wiener, and evenness measures, indicating more bacterial species, and increased bacterial diversity and abundance. These results suggest a potential relationship between Lactobacillus communities and the development and progression of rheumatoid arthritis.